Handbook for Environmental Risk Decision Making: Values, Perceptions, and Ethics - Cothern, C. Richard (CRC Press, 2009)
This handbook describes the broad aspects of risk management involving scientific policy judgment, uncertainty analysis, perception considerations, statistical insights, and strategic thinking. This book presents all the important concepts to enable the reader to "see the big picture." This ability is extremely important - it allows the decision maker or strategic environmental planner to understand and cope with a wide variety of complex and interlinked pieces of information and data.